Pain After Median Sternotomy: Collateral Damage or Mitigatable Byproduct? - Moon, Mi Hyoung; Kang, Joon Kyu; Kim, Hwan Wook; Jo, Keon Hyun; Choi, Soo Hwan; Song, Hyun (The Thoracic and Cardiovascular Surgeon, 2013)
Background Postoperative acute pain can cause anxiety and decrease the quality of life in patients. Acute sternal bone pain after cardiac surgery can persist for long time.Objective The aim of this study is to explore the relationships between the degree of sternal misalignment and the degree of acute sternal pain after coronary artery bypass grafting surgery (CABG).Methods We retrospectively reviewed postoperative coronary computed tomographic (CT) angiography and medical records in 104 patients who received CABG between May 1, 2009 and January 31, 2011. CT scan was classified into five categories, and we compared the degree of misalignment and subjective pain via numerical rating scale (NRS) system.Results Positive correlation was noted between NRS and the degree of sternal misalignment (Pearson correlation coefficient 0.660, p = 0.000).Conclusion Postoperative sternal pain is related to the degree of misalignment of the sternal halves. It would be appropriate for surgeons to approximate the sternal halves accurately to decrease the postoperative sternal wound pain in the first place.
Keywords: coronary artery bypass grafts surgery CABG; surgery/incisions; sternum